A method for preparing chitosan / calcium alginate composite monofilament

By adding calcium chloride to the chitosan solution and gel spinning with the sodium alginate solution, ion exchange with sodium alginate is performed by diffusion of calcium ions to form a chitosan/calcium alginate composite monofilament with good strength, the problem of difficulty in agglomeration of chitosan and sodium alginate mixture and coagulation of the spinning liquid is solved, and high strength and excellent mechanical properties are achieved.

CN116411365BActive Publication Date: 2025-03-11SHENZHEN XIANGGAN SCIENCE & TECHNOLOGY ACHIEVEMENTS TRANSFORMATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111683780.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-30
Publication Date
2025-03-11
Estimated Expiration
2041-12-30

AI Technical Summary

Technical Problem

The mixed solution of chitosan and sodium alginate is agglomerated due to the electrostatic attraction of opposite charges, making it difficult to prepare a uniform mixed solution, and the spinning solution is difficult to solidify quickly and easily break.

Method used

Add calcium chloride solution to the chitosan solution and gel spinning with the sodium alginate solution. Ion exchange with sodium alginate through the diffusion of calcium ions, forming a chitosan/calcium alginate composite gel with good strength, and forming a dense and uniform composite monofilament under gravity drafting.

Benefits of technology

Through the synergistic action of ion bonds and ion exchange, a high-strength chitosan/calcium alginate composite monofilament is formed, which solves the problems of difficulty in solidification of spinning liquid and poor mechanical properties of monofilament. The composite monofilament obtained has excellent performance, strength can reach more than 0.94cN/dtex, and the elongation of break is above 3.2%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116411365B_ABST
    Figure CN116411365B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a chitosan / calcium alginate composite monofilament, and belongs to the field of bio-based novel materials. The present invention promotes mutual complexation between chitosan and sodium alginate by adding calcium chloride solution to chitosan solution, and then gel spinning with sodium alginate solution, so that the molecular chains of sodium alginate and chitosan are entangled more closely, and the complexation state of the composite monofilament is well improved. At the same time, the calcium ions in the chitosan spinning solution undergo ion exchange with sodium alginate through diffusion, realize sol-gel transformation, obtain a gel with better strength, and can achieve gravity drafting of up to more than 10cm, so as to obtain a dense and uniform chitosan / calcium alginate composite monofilament. The chitosan / calcium alginate composite monofilament prepared by the present invention has excellent performance, and the strength can reach more than 0.94cN / dtex.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing chitosan / calcium alginate composite monofilament, and belongs to the field of bio-based new materials. Background Art

[0002] At present, chitosan fiber is mainly prepared by wet spinning. However, since the solid content of chitosan spinning solution is only 1.5-2.5%, the spinning solution is difficult to coagulate into fibers quickly after being ejected from the spinneret into the coagulation bath and is prone to breakage.

[0003] In the solution, the amino cations of chitosan (CS) interact with the negatively charged carboxyl anions of sodium alginate (SA) to form a polyelectrolyte complex through ionic bonds. For medical dressings, there is a synergistic effect between the two. Sodium alginate can absorb excess wound exudate, and chitosan provides antibacterial and hemostatic properties, thereby better improving the wound environment. Tongyao Zhao et al. combined the advantages of biodegradable fiber materials and polyelectrolyte (PEC) systems to prepare sodium alginate (SA) and quaternary ammonium chitosan composite fibers, which have advantages in wound dressings, medical gauze, medical absorbable sutures and tissue engineering. Lihong Fan et al. produced alginate-chitosan fibers by mixing chemically modified water-soluble chitosan with sodium alginate and then extruding it into a calcium chloride bath. The produced calcium alginate-(N,O)-carboxymethyl chitosan fibers were shown to have antibacterial activity after adding silver. Therefore, they can be the best choice for healthcare-related materials.

[0004] However, it is difficult to prepare a uniform chitosan and sodium alginate mixed solution because opposite charges in the solution will agglomerate through electrostatic attraction.

[0005] To solve these problems, many researchers have made some efforts, for example: Daiki Komoto et al. (Costalat M, Alcouffe P, David L, et al. Macro-hydrogels versus nanoparticles by the controlled assembly of polysaccharides [J]. Carbohydrate Polymers. 2015, 134: 541-546.) prepared oligomeric chitosan. Due to its low molecular weight, it can be dissolved in an alkaline aqueous solution and then mixed with a sodium alginate solution without immediate agglomeration, but through such modification, its mechanical properties are very weak; Watthanaphanit et al. (A. Watthanaphanit PST F. Novel chitosan-spotted alginate fibers from wet-spinning of alginate solutions containing emulsified chitosan–citrate complex and their characterization[J].Biomacromolecules,10(2009),pp.320-327.2009,10(1).) A novel speckled alginate chitosan fiber was produced by emulsifying unmodified chitosan and mixing it with sodium alginate and then extruding it into a calcium chloride bath. However, the distribution of chitosan along the length of these fibers was uneven and irregular. Summary of the invention

[0006] [Technical issues]

[0007] The amino cations of chitosan (CS) and the negatively charged carboxyl anions of sodium alginate (SA) will interact through ionic bonds, causing the blended solution to agglomerate into lumps, making it difficult to spin and the mechanical properties of the single fiber to be poor.

[0008] [Technical solution]

[0009] In order to solve the above problems, the present invention promotes the mutual complexation between chitosan and sodium alginate by adding calcium chloride solution to chitosan solution, and then gel spinning with sodium alginate solution, so that the molecular chains of sodium alginate and chitosan are entangled more tightly, and the complexation state of the composite monofilament is well improved. At the same time, the calcium ions in the chitosan spinning solution undergo ion exchange with sodium alginate through diffusion, realize sol-gel transformation, obtain a gel with good strength, and realize gravity drafting of up to 10 cm or more, thereby obtaining a dense and uniform chitosan / calcium alginate composite monofilament.

[0010] The first object of the present invention is to provide a method for preparing chitosan / calcium alginate composite monofilaments, comprising the following steps:

[0011] (1) mixing the chitosan solution and the calcium chloride solution uniformly to obtain a chitosan / calcium chloride mixed solution;

[0012] (2) placing a chitosan / calcium chloride mixed solution and a sodium alginate solution in two spinning solution boxes respectively, and performing gel spinning through a spinneret with a core-shell structure; wherein the chitosan / calcium chloride mixed solution is in the shell part and the sodium alginate solution is in the core part, and gravity stretching is performed, and the gravity stretching area is up to more than 10 cm;

[0013] (3) The composite gel after gravity drawing is washed, drawn, and dried to obtain the chitosan / calcium alginate composite monofilament.

[0014] In one embodiment of the spinning process of the present invention, the concentration of the chitosan solution in step (1) is 0.5-2% (mass percentage).

[0015] In one embodiment of the spinning of the present invention, the preparation method of the chitosan solution in step (1) is:

[0016] The chitosan was dissolved in an aqueous solution of acetic acid with a volume fraction of 2%; wherein the dissolution was carried out by stirring at 40° C. for 24 hours.

[0017] In one embodiment of the spinning of the present invention, the calcium chloride solution in step (1) is a calcium chloride aqueous solution with a mass concentration of 5-7%, more preferably 6%.

[0018] In one embodiment of the spinning process of the present invention, the amount of calcium chloride solution used in step (1) is 4-13% of the mass of the chitosan solution.

[0019] In one embodiment of the spinning of the present invention, after the mixing in step (1) is uniformly carried out, ultrasonic treatment is performed at a vibration frequency of 20 KHz for 15 minutes to remove bubbles.

[0020] In one embodiment of the spinning of the present invention, the device used for gel spinning in step (2) includes a chitosan / calcium chloride mixed solution spinning box, a sodium alginate solution spinning box, and a core-shell structure spinneret; wherein the core-shell structure spinneret comprises two coaxial tubular channels, and the nozzle is a core-shell structure with an outer diameter of 1.2 mm and an inner diameter of 0.7 mm.

[0021] In one embodiment of the spinning of the present invention, in step (2), a booster is used to place the chitosan / calcium chloride mixed solution and the sodium alginate solution in two spinning solution boxes at a speed of 0.5 mL / min.

[0022] In one embodiment of the spinning of the present invention, the gel spinning described in step (2) is that the two spinning solutions penetrate each other under the interaction of positive and negative ions, and replace each other at the spinneret interface. At the same time, with the help of the diffusion of calcium ions, ion exchange occurs with sodium alginate to form a coupling effect of gel, forming a composite gel; then the composite gel forms a gel with uniformly mixed components (not a core-shell structure) under gravity drawing.

[0023] In one embodiment of the spinning of the present invention, the water washing in step (3) is to put the composite gel into a water bath for water washing.

[0024] In one embodiment of the spinning of the present invention, the stretching in step (3) is to stretch the washed gel fiber, and the stretching multiple is 1.1-1.3 times.

[0025] In one embodiment of the spinning of the present invention, the drying in step (3) is carried out in air.

[0026] The second object of the present invention is the chitosan / calcium alginate composite monofilament prepared by the method of the present invention.

[0027] The third object of the present invention is to use the chitosan / calcium alginate composite monofilament of the present invention in the fields of wound dressings, medical gauze, medical absorbable sutures and tissue engineering.

[0028] [Beneficial Effects]

[0029] (1) The method of the present invention solves the agglomeration phenomenon of opposite charges of chitosan and sodium alginate mixed solution. Through the synergistic effect of ionic bonds formed between the positive charges of chitosan amino groups and the negative charges of sodium alginate carboxyl groups and the formation of gel by sodium alginate in the presence of calcium ions, a gel with a certain strength can be formed after the spinning solution is ejected from the spinneret, and gravity drawing can be performed. The gravity drawing area is as high as more than 10 cm.

[0030] (2) The present invention gradually forms a chitosan and calcium alginate composite gel with good strength through the synergistic effect of positive and negative ion bonds and ion exchange; then gravity drawing helps the molecular chains to be oriented along the axial direction of the fiber. At the same time, during the drawing process, chitosan molecules with amino positive charges and alginate molecules with carboxyl negative charges form ionic crosslinks; calcium ions gradually undergo ion exchange with sodium alginate through diffusion to form calcium alginate. All of these help to form high-strength chitosan / calcium alginate composite monofilaments.

[0031] (3) The present invention puts the gravity-stretched gel into water for washing, further solidifies the chitosan, and then dries it. During the drying process, it is stretched (stretching ratio 1.1-1.3 times) to obtain chitosan / calcium alginate composite monofilaments.

[0032] (4) The chitosan / calcium alginate composite monofilament prepared by the present invention has excellent performance, with a strength of more than 0.94 cN / dtex and an elongation at break of more than 3.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a diagram of the spinning device.

[0034] Figure 2 SEM images of the fracture surface and longitudinal surface of the composite monofilament, where a and c are the CS / SA composite monofilament of comparative example 1, a is the fracture surface, and c is the longitudinal surface; b and d are the CS / CA composite monofilament of embodiment 1, b is the fracture surface, and d is the longitudinal surface.

[0035] Figure 3 : is the EDS N element distribution diagram of the composite monofilament, wherein a is the CS / SA composite monofilament of comparative example 1; b is the CS / CA composite monofilament of example 1.

[0036] Figure 4 FT-IR spectra of CS fiber, CS / SA composite monofilament, CS / CA composite monofilament and SA fiber.

[0037] Figure 5 1 and 2 are X-ray diffraction patterns of the CS / SA composite monofilament of Comparative Example 1 and the CS / CA composite monofilament of Example 1.

[0038] Figure 6 These are the thermal stability test results of the CS / SA composite monofilament of Comparative Example 1 and the CS / CA composite monofilament of Example 1; wherein a is the TG curve; and b is the DTG curve.

[0039] Figure 7 are the extensional rheological properties of the spinning solution, where a is the extensional rheological properties of the chitosan spinning solution with different amounts of calcium chloride solution; b is the extensional rheological properties of the spinning solution of sodium alginate and chitosan / sodium alginate; c is the chitosan / sodium alginate complex with added calcium ions; d is the chitosan / sodium alginate complex without added calcium ions.

[0040] Figure 8 The states of the composite monofilaments obtained with different amounts of calcium chloride solution entering water; among them, a is 0%-dry; b is 0%-swelling; c is 4%-dry; d is 4%-swelling; e is 7%-dry; f is 7%-swelling; g is 10%-dry; h is 10%-swelling; i is 13%-dry; and j is 13%-swelling.

[0041] Fig. 9 It is the complexation state of chitosan solution with different concentrations and sodium alginate solution with different concentrations. DETAILED DESCRIPTION

[0042] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0043] Test method:

[0044] 1. Morphological characterization: A HITACHI SU1510 electron microscope (Hitachi, Ltd., Japan) was used to observe the cross-sectional and longitudinal surface morphologies of the composite monofilaments that were brittlely broken by liquid nitrogen. The two composite monofilaments that had passed the constant temperature and humidity balance were placed on the conductive glue and sprayed with gold, and then observed under an electron microscope with an accelerating voltage of 5 kV.

[0045] 2. N element distribution and content test: By using EDX (Zeiss, Germany) scanning electron microscope to photograph the structure of the wire cross section, we can know the atomic composition of the cross section. Since calcium atoms are the characteristics of calcium alginate and nitrogen atoms are the characteristics of chitosan, we can know the content and distribution of chitosan and alginate in the cross section of the composite monofilament. The two wire samples after constant temperature and humidity balance were placed on the conductive glue, and after gold spraying, the composite monofilament was subjected to elemental analysis at an acceleration voltage of 15kV.

[0046] 3. Fourier transform infrared spectroscopy: The composite monofilament was placed in a vacuum oven and dried at 50°C for 24 hours, then -1 The resolution recorded is 4000 to 450 cm -1 Infrared absorption spectrum in the range.

[0047] 4. Crystal structure test: The crystal structure of the silk was analyzed using a D8 Advance X-ray diffractometer (Bruker AXS GmbH, Germany). The sample was scanned at a rate of 4° / min, with a scanning range of 10°-60° and a step length of 0.02°.

[0048] 5. Tensile mechanical properties test: The mechanical properties of the yarn were tested by a single fiber strength tester (YG004D Changzhou No. 2 Textile Instrument Factory). The gauge length was set to 20 mm, and the crosshead speed was set to 20 mm / min; the breaking strength (cN / dtex) and breaking elongation (%) of the sample yarn were tested respectively, and at least 50 fibers of each sample were tested repeatedly and the average value was calculated.

[0049] 6. Thermal stability test: The thermal stability of the wire was analyzed by a thermal analysis system (TA-Q500, TA Instruments, USA). The sample was heated from 50°C to 800°C at a heating rate of 20°C / min in a nitrogen gas flow rate of 50 mL / min, and the sample mass range was 5 mg.

[0050] 7. Water swelling performance test: Weigh the composite monofilament after constant temperature and humidity balance, and then soak multiple sample composite monofilaments in a certain amount of distilled water at room temperature for different time periods (5min, 10min, 15min, 20min, 25min, 30mins, 35min, 40min, 45min, 50min, 55min, 60min) to make them fully swell. Take the swollen monofilaments out of the distilled water, dry their surface with filter paper and weigh the mass. The swelling performance is expressed by the swelling ratio R, and the calculation formula of R is as follows (1):

[0051]

[0052] Where R is the swelling ratio; W d is the mass of the composite monofilament after swelling; W0 is the mass of the dry composite monofilament; each sample is tested at least three times and the average value is calculated.

[0053] Chitosan (viscosity 1250 mPa.s, deacetylation degree 93%) used in the examples was purchased from Weifang Haizhiyuan Biological Products Co., Ltd.; sodium alginate (viscosity 740 mPa.s, purity>90wt%), anhydrous calcium chloride, and acetic acid (all analytically pure) were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0054] The device used for gel spinning in the embodiment includes a chitosan / calcium chloride mixed solution spinning box, a sodium alginate solution spinning box, a core-shell structure spinneret, and a washing tank; wherein the chitosan / calcium chloride mixed solution spinning box is connected to the spinneret shell part, and the sodium alginate solution spinning box is connected to the spinneret core part; the core-shell structure spinneret comprises two coaxial tubular channels, and the nozzle is a core-shell structure with an outer diameter of 1.2 mm and an inner diameter of 0.7 mm; specifically, Figure 1 .

[0055] Example 1

[0056] A method for preparing chitosan / calcium alginate composite monofilament comprises the following steps:

[0057] (1) Dissolving chitosan in a 2% (v / v) acetic acid aqueous solution and mechanically stirring in a water bath at 40° C. for 24 h to obtain a chitosan solution with a mass concentration of 2%; dissolving calcium chloride in water to obtain a calcium chloride aqueous solution with a mass fraction of 6%; then mixing the chitosan solution and the calcium chloride solution to obtain a chitosan / calcium chloride mixed solution; wherein the amount of the calcium chloride solution is 7% of the mass of the chitosan solution;

[0058] (2) dissolving sodium alginate in water to obtain a sodium alginate aqueous solution with a mass concentration of 1.5%;

[0059] (3) using a booster, placing a chitosan / calcium chloride mixed solution in a spinning solution box connected to the shell part of the spinneret at a speed of 0.5 mL / min; placing a sodium alginate solution in a spinning solution box connected to the core part of the spinneret; performing gel spinning through a spinneret with a core-shell structure, the two spinning solutions mutually permeate under the interaction of positive and negative ions, and replace at the spinneret interface, while at the same time, with the help of the diffusion of calcium ions, ion exchange occurs with sodium alginate to form a coupling effect of gel, forming a composite gel, and then forming a gel with uniformly mixed components (not a core-shell structure) under a gravity stretch of up to 10 cm;

[0060] (3) The composite gel after gravity stretching is placed in a water bath for washing; the washed gel fiber is then stretched (stretching factor 1.2), and finally dried in air to obtain the chitosan / calcium alginate composite monofilament.

[0061] Comparative Example 1

[0062] The calcium chloride solution in step (1) of Example 1 was omitted, and the other steps were the same as in Example 1 to obtain chitosan / sodium alginate (CS / SA) composite monofilaments.

[0063] The composite monofilaments obtained in Example 1 and Comparative Example 1 were subjected to performance tests, and the test results are as follows:

[0064] Figure 2 Figure 1 is a SEM image of the fracture surface and longitudinal surface of the composite monofilament, where a and c are the CS / SA composite monofilament of Comparative Example 1, a is the fracture surface, c is the longitudinal surface; b and d are the CS / CA composite monofilament of Example 1, b is the fracture surface, d is the longitudinal surface. Figure 2 It can be seen that chitosan with added calcium ions has good compatibility with sodium alginate. Compared with CS / SA composite monofilaments, CS / CA composite monofilaments have smooth cross-sections, fewer grooves, uniform structures, and no obvious changes in the longitudinal surface.

[0065] Figure 3 is the EDS N element distribution diagram of the composite monofilament, where a is the CS / SA composite monofilament of comparative example 1; b is the CS / CA composite monofilament of example 1. Table 1 shows the content of each element in the cross section of the composite monofilament. Figure 3It can be seen from Table 1 that the N element is evenly distributed in the cross section of the CS / CA composite monofilament of Example 1 with calcium ions added, and the content is 46.49%, while the N element in the cross section of the CS / SA composite monofilament of Comparative Example 1 without calcium ions added is 17.57%; this is because in the chitosan solution, the addition of calcium ions increases the electrostatic complexation with sodium alginate, so that the chitosan solution and the sodium alginate solution coagulate and crosslink at the same time, and the calcium ions also non-covalently crosslink with sodium alginate, so that the content of chitosan in the composite monofilament is increased. More chitosan means more N element. According to calculations, before complexation, the sodium ion content in the spinning fluid is twice that of the calcium ion content. During complexation, the calcium ions replace part of the sodium, and the chitosan also crosslinks part of it. After washing part of it with water, due to some limitations of the spinning device itself, a little sodium element is still left in the CS / CA composite monofilament.

[0066] Table 1 Content of each element in the cross section of composite monofilament

[0067]

[0068] Figure 4 FT-IR spectra of CS fiber, CS / SA composite monofilament, CS / CA composite monofilament and SA fiber. Figure 4 It can be seen that CS is at 1649cm -1 and 1591cm -1 There are two absorption peaks at 1673cm, which are the C=O stretching vibration peak of amide I and the NH plane deformation peak of amide II. -1 and 1475cm -1 The peaks at 1649cm-1 are the asymmetric and symmetric stretching vibration absorption peaks of -COO-; CS at 1649cm-1 -1 and 1591cm -1 The peak of disappearance in CS / SA and CS / CA may be due to the protonation of -NH2 to -NH3 + -COO- in SA at 1673cm -1 and 1475cm -1 The characteristic peaks at 1591 cm -1 and 1414cm -1 , indicating that -COO- and -NH3 + and Ca 2+ Ionic cross-linking occurs; at 3500-3200cm -1 The peak of OH stretching vibration in CS / CA becomes narrower, indicating that the hydrogen bond between CS / CA is weakened and the ability to absorb water molecules is reduced. In addition, a new peak appears at 2833 cm -1After the formation of CS / CA, part of -COO- may be protonated. The IR results also show the electrostatic interaction between CS and SA and calcium ions.

[0069] Figure 5 The X-ray diffraction patterns of the CS / SA composite monofilament of Comparative Example 1 and the CS / CA composite monofilament of Example 1 are shown in FIG. Figure 5 It can be seen that the shapes and sizes of the diffraction peaks of CS / SA composite monofilaments and CS / CA composite monofilaments are similar; CS / SA composite monofilaments and CS / CA composite monofilaments both show two main peaks at 14° and 20°. The crystallinity of CS / CA is improved, and the mechanical properties are improved.

[0070] Figure 6 The thermal stability test results of the CS / SA composite monofilament of comparative example 1 and the CS / CA composite monofilament of example 1 are shown in Figure 1; a is the TG curve; b is the DTG curve. Figure 6 It can be seen that the initial thermal decomposition temperature of the CS / CA composite monofilament with the addition of calcium ions is higher than that of the CS / SA composite monofilament. At the highest thermal decomposition rate, the temperature corresponding to the CS / CA composite monofilament increased by 10°C. These results all indicate that the addition of calcium ions can improve the thermal stability of the composite monofilament.

[0071] Example 2

[0072] The amount of calcium chloride solution in step (1) of Example 1 was adjusted to 4, 10, and 13% of the mass of the chitosan solution; the other conditions were kept consistent with Example 1 to obtain a composite monofilament.

[0073] The composite monofilaments obtained in Examples 1 and 2 and Comparative Example 1 were subjected to performance tests, and the test results are as follows:

[0074] Figure 7 is the extensional rheological property of the spinning solution, where a is the extensional rheological property of the chitosan spinning solution with different amounts of calcium chloride solution; b is the extensional rheological property of the spinning solution of sodium alginate and chitosan / sodium alginate; c is the chitosan / sodium alginate complex with added calcium ions; d is the chitosan / sodium alginate complex without added calcium ions. Figure 7 It can be seen from figure a that the breaking time of the spinning solution blended with different amounts of calcium chloride solution and chitosan from the beginning of stretching into fluid filaments to breaking first increases and then decreases. Obviously, compared with the pure chitosan spinning solution, it takes longer time for the blended spinning solution to be stretched into fluid filaments to the same diameter after adding an appropriate amount of calcium chloride solution. The extension of the breaking time indicates that the ductility of the spinning solution is improved, the molecular chains of the fluid filaments are better arranged, and thus the mechanical properties of the composite monofilaments can also be improved. Figure 7As can be seen in Figure b: After the 2% chitosan solution and the 1.5% sodium alginate solution are mixed and agglomerated, the elongational rheology of the mixed solution is significantly improved compared with that of the single solution. Figure 7 In c and d, we can see: the blended state of chitosan and sodium alginate with calcium chloride added and the blended state of chitosan and sodium alginate without calcium ions added. The results show that after adding calcium chloride, chitosan and sodium alginate are better combined. It may be that the calcium ions in the calcium chloride solution exchange ions with the sodium ions in the sodium alginate to form a network structure, which is easier to electrostatically complex with chitosan. At the same time, calcium ions replace sodium ions to generate calcium alginate.

[0075] Table 2 shows the tensile mechanical properties of chitosan spinning solutions with different amounts of calcium chloride solution. It can be seen from Table 2 that when the amount of calcium chloride solution is 7% of the mass of the chitosan solution, the breaking strength of the composite monofilament reaches the maximum, which is 1.14cN / dtex, which is 55.4% higher than before the addition of calcium chloride solution. With the increase of the amount of calcium chloride solution, the elongation at break increases continuously, while the breaking strength of the composite monofilament increases first and then decreases. When the amount of calcium chloride solution is small, the number of calcium ions bound to the chitosan macromolecules is small, and the cross-linking points in the composite monofilament are small, which makes the intermolecular force weak and the strength of the silk is small. With the increase of the amount of calcium chloride solution, the number of calcium ions bound to the chitosan macromolecules increases, the cross-linking points in the silk increase, and the strength increases. However, when the amount of calcium chloride solution is too high, the diffusion rate of calcium ions is fast, and it will quickly combine with chitosan macromolecules on the silk surface to form a dense cortex, which hinders the diffusion of calcium ions into the silk and the diffusion of sodium ions in the silk to the outer layer, so that the cross-linking points in the silk are reduced, thereby reducing the strength.

[0076] Table 2 Tensile mechanical properties of chitosan spinning solution with different amounts of calcium chloride solution

[0077] <![CDATA[Dosage of CaCl2 (%)]]> Breaking strength / (cN / dtex) Elongation at break (%) 0 0.747 2.452 4 0.94 3.238 7 1.142 3.585 10 1.01 3.856 13 0.893 4.229

[0078] Figure 8 The states of the composite monofilaments obtained with different amounts of calcium chloride solution entering water; a is 0%-dry; b is 0%-swelling; c is 4%-dry; d is 4%-swelling; e is 7%-dry; f is 7%-swelling; g is 10%-dry; h is 10%-swelling; i is 13%-dry; j is 13%-swelling. Figure 8 It can be seen that: the composite monofilament without calcium ions partially disintegrated during the swelling process, and after swelling, the strength was lower than that of other composite monofilaments, but the swelling degree was the largest. Through experimental calculations, it was found that the amount of calcium ions had little effect on the swelling degree of the composite monofilament (the trend of the swelling degree was gradually weakened), but from the appearance of the composite monofilament after swelling, when the calcium ion dosage was 7%, the composite monofilament after swelling was more transparent and uniform. The swelling experiment also proved that with the increase in the number of crosslinking points, the swelling was gradually suppressed.

[0079] Table 3 shows the swelling ratio of the composite monofilaments obtained with different amounts of calcium chloride solution after being immersed in water for different times. It can be seen from Table 3 that the swelling ratio of all composite monofilaments increased significantly from the initial 5 minutes to 20 minutes, and remained basically constant after 20 minutes. These results show that it takes about 20 minutes for all composite monofilaments to reach swelling equilibrium. The swelling ratio decreases with the increase of calcium ion dosage. The swelling ratio of the composite monofilament without calcium ions is the highest at the same swelling time. The mixed structure formed by chitosan and sodium alginate is conducive to the penetration of water into the fiber. With the increase of calcium ion concentration, the amino groups in chitosan will be consumed due to the cross-linking reaction, and the ability of cross-linked chitosan to form hydrogen bonds with water molecules is reduced, resulting in a decrease in the degree of equilibrium swelling.

[0080] Table 3 Swelling ratio of composite monofilaments obtained with different amounts of calcium chloride solution after soaking in water for different times

[0081]

[0082] Example 3

[0083] The concentrations of chitosan and sodium alginate in Example 1 were adjusted to 0.5, 1.0, 1.5, 2.0 and 2.5%, and the concentrations of sodium alginate were adjusted to 0.5, 1.0, 1.5, 2.0 and 2.5%, respectively, and the other conditions were kept consistent with Example 1 to obtain a spinning solution.

[0084] The obtained spinning solution was subjected to performance test, and the test results are as follows:

[0085] Fig. 9 The complexation states of chitosan solutions with different concentrations and sodium alginate solutions with different concentrations. Fig. 9 It can be seen that complexation is a rapid process. Within this experimental range (0-2% spinning solution solubility), the concentration of CS solution should not be less than the solubility of SA solution (black area). The diffusion effect of positive and negative charged polyelectrolytes is good, which can ensure spinnability. Black dots indicate that the fluid complexation state is good, while polygons indicate that the fluid complexation state is poor (water droplets are constantly formed along the spinning fluid, there are gaps on the surface of the fluid, the structure is uneven, and it is easy to break). It may be that the cationic polyelectrolytes with higher molecular weight in the outer layer can form a more viscous complex to stabilize the interface, so their suction is better and promotes complexation. Therefore, 2% CS and 1.5% SA were selected to make composite monofilaments.

[0086] Comparative Example 2

[0087] A method for preparing chitosan / calcium alginate composite monofilament comprises the following steps:

[0088] (1) dissolving chitosan in a 2% (v / v) acetic acid aqueous solution and mechanically stirring in a 40° C. water bath for 24 h to obtain a chitosan solution with a mass concentration of 2%;

[0089] (2) dissolving sodium alginate in water to obtain a sodium alginate aqueous solution with a mass concentration of 1.5%;

[0090] (3) using a booster, placing a chitosan solution in a spinning solution box connected to the shell part of the spinneret at a rate of 0.5 mL / min; placing a sodium alginate solution in a spinning solution box connected to the core part of the spinneret; performing gel spinning through a spinneret with a core-shell structure; and then forming a gel with uniformly mixed components (not a core-shell structure) under gravity drawing up to 10 cm;

[0091] (4) The chitosan / sodium alginate fiber that has been stretched by gravity is directly placed in a 6% calcium chloride solution for coagulation to obtain a chitosan / calcium alginate composite monofilament.

[0092] The obtained chitosan / calcium alginate composite monofilament was tested, and the test results are as follows:

[0093] The breaking strength of chitosan / calcium alginate composite monofilament is only 0.20 cN / dtex, the breaking elongation is 10%, and there is almost no swelling. This is because chitosan / sodium alginate coagulates quickly in calcium chloride solution and the orientation degree of fiber macromolecules is low.

[0094] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing chitosan / calcium alginate composite monofilament, characterized in that: The steps include: (1) Mixing chitosan solution and calcium chloride solution evenly to obtain a chitosan / calcium chloride mixed solution; the mass concentration of the chitosan solution is 2%; the calcium chloride solution is a calcium chloride aqueous solution with a mass concentration of 6%; the amount of the calcium chloride solution is 7% of the mass of the chitosan solution; (2) placing a chitosan / calcium chloride mixed solution and a sodium alginate solution in two spinning solution boxes respectively, and performing gel spinning through a core-shell structure spinneret; wherein the chitosan / calcium chloride mixed solution is in the shell part, and the sodium alginate solution is in the core part, and gravity stretching is performed, and the gravity stretching area is up to more than 10 cm; the sodium alginate solution is a sodium alginate aqueous solution with a mass concentration of 1.5%; (3) The composite gel after gravity drawing is washed, drawn, and dried to obtain the chitosan / calcium alginate composite monofilament.

2. The method according to claim 1, characterized in that The device used for gel spinning in step (2) includes a chitosan / calcium chloride mixed solution spinning box, a sodium alginate solution spinning box, and a core-shell structure spinneret; wherein the core-shell structure spinneret comprises two coaxial tubular channels, and the nozzle is a core-shell structure with an outer diameter of 1.2 mm and an inner diameter of 0.7 mm.

3. The method according to claim 1, characterized in that The gel spinning described in step (2) is that the two spinning solutions penetrate each other under the interaction of positive and negative ions, and replace each other at the spinneret interface. At the same time, with the help of the diffusion of calcium ions, ion exchange occurs with sodium alginate to form a coupling effect of gel, forming a composite gel; then the composite gel forms a gel with uniformly mixed components under gravity drawing.

4. The method according to claim 1, characterized in that: The stretching described in step (3) is to stretch the washed gel fiber, and the stretching multiple is 1.1-1.3 times.

5. The method according to claim 1, characterized in that The preparation method of the chitosan solution described in step (1) is: dissolving chitosan in an acetic acid aqueous solution with a volume fraction of 2%.

6. Chitosan / calcium alginate composite monofilament prepared by the method according to any one of claims 1 to 5.

7. Use of the chitosan / calcium alginate composite monofilament according to claim 6 in the fields of wound dressings, medical gauze, medical absorbable sutures and tissue engineering.

Citation Information

Patent Citations

  • Chitosan / calcium alginate needleless electrospinning nanofiber membrane for medical dressings and preparation method thereof

    CN109267240A

  • Chitose graft alginate fibre, its production and use

    CN1940153A